Ngemong Tradition In Madrasah Leadership Management in Madrasah - Muhamad Busro; Akhmad Sirojuddin; Abu Darim; Dewi Afiatul Qutsiyah (Chalim Journal of Teaching and Learning (CJoTL), 2022)
The purpose of this study was to determine and analyze the leadership of the head of Madrasah based on the management function that conceptualizes the tradition of ngemong in MA Taqwal IIah Tunggu Meteseh Tembalang Semarang. This type of research uses a qualitative case study approach. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques are carried out by collecting data, reducing data, presenting data, drawing conclusions. To check the validity of the data, the researchers used credibility and triangulation tests. The results of this study found that 1. The planning of the tradition of ngemong in the leadership of the Kamad at the Taqwal IIah Waiting for Meteseh Tembalang Semarang, a) The type of leadership of the head of the madrasah is a charismatic leadership type., b) Planning of the head of the madrasa begins by determining the medium-term plan and the long-term plan for the madrasa year. Then the plan was followed up with a madrasa work meeting. 2. Organizing the tradition of ngemong in the leadership of the Kamad at MA Taqwal IIah Waiting for Meteseh Tembalang Semarang, a) The way of organizing the head of the madrasa begins with carrying out work meetings related to the discussion of the madrasa program which is contained in the medium-term and long-term plans for the madrasa year., b) The headmaster Madrasah mandates the waka of curriculum and waka of student affairs to accommodate all madrasa activities or programs in accordance with their respective jobdesk. 3. Implementation of the tradition of ngemong in the leadership of Kamad at MA Taqwal IIahWait for Meteseh Tembalang Semarang, a) The head of the madrasah provides direction and primarily motivation to all madrasah residents, be it the teacher council, education staff, or to the students themselves., b) The madrasa head supervises and evaluate both those relating to the performance of teachers and education personnel, as well as all activities that have been and will be carried out by the madrasah.